Tìm x
x-2=(x-2)^2
(x^2+1)(2x-1)+2x=1
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x\left(x-2\right)+x-2=0\\ \Leftrightarrow x\left(x-2\right)+\left(x-2\right)=0\\ \Leftrightarrow\left(x-2\right)\left(x+1\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x-2=0\\x+1=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=2\\x=-1\end{matrix}\right.\)
\(x^2-2x+1=9\\ \Leftrightarrow\left(x-1\right)^2=9\\ \Leftrightarrow\left[{}\begin{matrix}x-1=-3\\x-1=3\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=-2\\x=4\end{matrix}\right.\)
\(7x^2=2x\\ \Leftrightarrow7x^2-2x=0\\ \Leftrightarrow x\left(7x-2\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=0\\7x-2=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=0\\x=\dfrac{2}{7}\end{matrix}\right.\)
\(x^2-6x=8\\ \Leftrightarrow x^2-6x-8=0\\ \left(x^2-6x+9\right)-17=0\\ \Leftrightarrow\left(x-3\right)^2-\sqrt{17^2}=0\\ \Leftrightarrow\left(x-3-\sqrt{17}\right)\left(x-3+\sqrt{17}\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x-3-\sqrt{17}=0\\x-3+\sqrt{17}=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=3+\sqrt{17}\\x=3-\sqrt{17}\end{matrix}\right.\)
a) (2x+12x−1−2x−12x+1):4x10x−5=(2x+1)2−(2x−1)2(2x−1)(2x+1).10x+54x(2x+12x−1−2x−12x+1):4x10x−5=(2x+1)2−(2x−1)2(2x−1)(2x+1).10x+54x
=4x2+4x+1−4x2+4x−1(2x−1)(2x+1).5(2x+1)4x4x2+4x+1−4x2+4x−1(2x−1)(2x+1).5(2x+1)4x
=8x.5(2x+1)(2x−1)(2x+1).4x=102x−18x.5(2x+1)(2x−1)(2x+1).4x=102x−1
b) (1x2+x−2−xx+1):(1x+x−2)(1x2+x−2−xx+1):(1x+x−2)
=(1x(x+1)+x−2x+1):1+x2−2xx(1x(x+1)+x−2x+1):1+x2−2xx
=1+x(x−2)x(x+1).xx2−2x+11+x(x−2)x(x+1).xx2−2x+1
=(x2−2x+1)xx(x+1)(x2−2x+1)=1x+1(x2−2x+1)xx(x+1)(x2−2x+1)=1x+1
c) 1x−1−x3−xx2+1.(1x2−2x+1+11−x2)1x−1−x3−xx2+1.(1x2−2x+1+11−x2)
=1x−1−x3−xx2+1.[1(x−1)2−1(x−1)(x+1)]
a) (2x+12x−1−2x−12x+1):4x10x−5(2x+12x−1−2x−12x+1):4x10x−5
= 0 - 0
= 0
b) (1x2+x−2−xx+1):(1x+x−2);(1x2+x−2−xx+1):(1x+x−2)
= (x-xx+1) : (2x-2) : (x-xx+1) : (2x-2)
c) 1x−1−x3−xx2+1.(1x2−2x+1+11−x2)
= -2x-1-xx2+1. (14 - 4x)
= -x2-1-xx2+14-4x
= -6x-xx2+13
1) x - 2 = ( x - 2 )2
<=> ( x - 2 ) - ( x - 2 )2 = 0
<=> ( x - 2 )[ 1 - ( x - 2 ) ] = 0
<=> ( x - 2 )( 1 - x + 2 ) = 0
<=> ( x - 2 )( 3 - x ) = 0
<=> \(\orbr{\begin{cases}x-2=0\\3-x=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=2\\x=3\end{cases}}\)
2) ( x2 + 1 )( 2x - 1 ) + 2x = 1
<=> ( x2 + 1 )( 2x - 1 ) + ( 2x - 1 ) = 0
<=> ( 2x - 1 )[ ( x2 + 1 ) + 1 ] = 0
<=> ( 2x - 1 )( x2 + 1 + 1 ) = 0
<=> ( 2x - 1 )( x2 + 2 ) = 0
<=> \(\orbr{\begin{cases}2x-1=0\\x^2+2=0\end{cases}}\Leftrightarrow x=\frac{1}{2}\)( do x2 + 2 ≥ 2 > 0 ∀ x )